Long-term effect of sleeve gastrectomy vs Roux-en-Y gastric bypass in people living with severe obesity: a phase III multicentre randomised controlled trial (SleeveBypass)Research in context - L Ulas Biter; Judith WH. 't Hart; Bo J. Noordman; J Frans Smulders; Simon Nienhuijs; Martin Dunkelgrün; Johannes F. Zengerink; Erwin Birnie; Irene AM. Friskes; Guido HH. Mannaerts; Jan A. Apers (Elsevier, 2024)
Summary: Background: Sleeve gastrectomy is the most performed metabolic surgical procedure worldwide. However, conflicting results offer no clear evidence about its long-term clinical comparability to Roux-en-Y gastric bypass. This study aims to determine their equivalent long-term weight loss effects. Methods: This randomised open-label controlled trial was conducted from 2012 until 2017 in two Dutch bariatric hospitals with a 5-year follow-up (last follow-up July 29th, 2022). Out of 4045 patients, 628 were eligible for metabolic surgery and were randomly assigned to sleeve gastrectomy or Roux-en-Y gastric bypass (intention-to-treat). The primary endpoint was weight loss, expressed by percentage excess body mass index (BMI) loss. The predefined clinically relevant equivalence margin was −13% to 13%. Secondary endpoints included percentage total kilograms weight loss, obesity-related comorbidities, quality of life, morbidity, and mortality. This trial is registered with Dutch Trial Register NTR4741: https://onderzoekmetmensen.nl/nl/trial/25900. Findings: 628 patients were randomised between sleeve gastrectomy (n = 312) and Roux-en-Y gastric bypass (n = 316) (mean age 43 [standard deviation (SD), 11] years; mean BMI 43.5 [SD, 4.7]; 81.8% women). Excess BMI loss at 5 years was 58.8% [95% CI, 55%-63%] after sleeve gastrectomy and 67.1% [95% CI, 63%-71%] after Roux-en-Y gastric bypass (difference 8.3% [95% CI, −12.5% to −4.0%]). This was within the predefined margin (P < 0.001). Total weight loss at 5 years was 22.5% [95% CI, 20.7%-24.3%] after sleeve gastrectomy and 26.0% [95% CI, 24.3%-27.8%] after Roux-en-Y gastric bypass (difference 3.5% [95% CI, −5.2% to −1.7%]). In both groups, obesity-related comorbidities significantly improved after 5 years. Dyslipidaemia improved more frequently after Roux-en-Y gastric bypass (83%, 54/65) compared to sleeve gastrectomy (62%, 44/71) (P = 0.006). De novo gastro-oesophageal reflux disease occurred more frequently after sleeve gastrectomy (16%, 46/288) vs Roux-en-Y gastric bypass (4%, 10/280) (P < 0.001). Minor complications were more frequent after Roux-en-Y gastric bypass (5%, 15/316) compared to sleeve gastrectomy (2%, 5/312). No statistically significant differences in major complications and health-related quality of life were encountered. Interpretation: In people living with obesity grades 2 and 3, sleeve gastrectomy and Roux-en-Y gastric bypass had clinically comparable excess BMI loss according to the predefined definition for equivalence. However, Roux-en-Y gastric bypass showed significantly higher total weight loss and significant advantages in secondary outcomes, including dyslipidaemia and GERD, yet at a higher rate of minor complications. Major complications, other comorbidities, and overall HRQoL did not significantly differ between the groups. Funding: Not applicable.